Experimental investigations on dynamic gelation and consistency hump during the thickening time of cement slurries - Hasan Maroof; Mohsen Dehvedar; Ali Barati-Harooni; Reza Mohammad-Hashem (Case Studies in Construction Materials)
Proper cement slurry design is crucial for oil well cementing operations to control its fluidity until it reaches the desired point. A well-designed cement slurry can greatly enhance the quality of oil well-cementing jobs, especially in complex situations like high-pressure, high-temperature (HPHT) conditions. The study investigated the thickening time of cement slurry and other parameters, including plastic viscosity (PV), yield point (YP), and fluid loss (FL). It also explored the simultaneous effects of salt and retarder on both normal and heavyweight cement slurries. To achieve this, different cement slurries were prepared with varying salt content and various amounts of retarders while keeping the other additives constant across all formulations. The thickening time test was conducted using an HPHT consistometer to analyze how these additives affected the thickening time and other properties of the slurry. The findings revealed that salt can act as a lubricant, reducing the rheological characteristics of the slurry, but it also increases fluid loss. Additionally, a dynamic gelation and consistency hump was observed for slurries with salt content ranging from 24 % to 30 %, an important consideration during cementing operations. Analyzing the thickening time graphs throughout the pumping time interval can predict potential pressure-related pumping problems.